On Space, Place, and Form in Herodotus’ Histories - Barker, E. T. E. (Histos, 2021)
This article reflects on how our own technological developments can help us see Herodotus’ archetype of historical inquiry in a new light. It explores various aspects of place in the Histories—as spaces that are lived, constructed, and relational—to show how and why the idea of place can be such a powerful means for linking information and understanding the past. In discussing the role of place in structuring Herodotus’ narrative, it argues that the potential for linking is afforded by the new prose medium. By virtue of those linkages, Herodotus’ account differs in its spatial configurations from earlier, oral-based narratives.